2015
DOI: 10.3390/rs71014179
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Fluorescence Parameters for Crop Leaves with Bayesian Inversion

Abstract: Abstract:In this study, backward and forward fluorescence radiance within the emission spectrum of 640-850 nm were measured for leaves of soybean, cotton, peanut and wheat using a hyperspectral spectroradiometer coupled with an integration sphere. Fluorescence parameters of crop leaves were retrieved from the leaf hyperspectral measurements by inverting the FluorMODleaf model, a leaf-level fluorescence model able to simulate chlorophyll fluorescence spectra for both sides of leaves. This model is based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The reason for the low accuracy of ↑FY739 and ↓FY739 for the LNC is the strong self-absorption of chlorophyll in the red region rather than in the far-red region. The red peak of SIF is more likely to be closely correlated to the LNC than the far-red peak, which agrees with previous study [52]. Although the downward SIF signal was weaker than that of the upward SIF, the correlation coefficient between the LNC and the downward SIF was higher than that with the upward SIF.…”
Section: Power Of the Upward And Downward Sif Yield Indices (↑Fy And supporting
confidence: 91%
See 1 more Smart Citation
“…The reason for the low accuracy of ↑FY739 and ↓FY739 for the LNC is the strong self-absorption of chlorophyll in the red region rather than in the far-red region. The red peak of SIF is more likely to be closely correlated to the LNC than the far-red peak, which agrees with previous study [52]. Although the downward SIF signal was weaker than that of the upward SIF, the correlation coefficient between the LNC and the downward SIF was higher than that with the upward SIF.…”
Section: Power Of the Upward And Downward Sif Yield Indices (↑Fy And supporting
confidence: 91%
“…Figure 12A,B,C also show that the value of the downward SIF yield indices (↓FY687 and ↓FY739) are generally lower than that in the upward fluorescence (↑FY687 and ↑FY739). Due to the stronger absorption, scattering effect for the SIF emission [52], and more chlorophyll content around the upper epidermis, it was observed that the upward SIF radiance and SIF yield indices were higher compared with that of the downward SIF, especially for the SIF peak in the red region, which is consistent with [40,53]. Much of the light is absorbed by the palisade parenchyma, in the view of light propagation in the leaves.…”
Section: Power Of the Upward And Downward Sif Yield Indices (↑Fy And supporting
confidence: 56%
“…Chlorophyll content (C ab , in unit of μg/cm 2 ), carotenoid content (C ca , in unit of μg/cm 2 ), water content (C w , in unit of g/cm 2 ), and dry matter content (C dm , in unit of g/cm 2 ), were measured for the leaves and used to evaluate the inverted results as introduced below. Detailed description of the measurement protocol and data processing can be found in Zhao et al (2015b).…”
Section: Leaf Hyperspectral Measurementsmentioning
confidence: 99%
“…Zhao et al [1] showcase their attempt at inverting crop leaf fluorescence parameters from the leaf-level fluorescence model, FluorMODleaf. As a simpler and more straightforward approach, spectral indices have received more attention in this Special Issue.…”
Section: Overview Of Contributionsmentioning
confidence: 99%